Understanding EFL learners’ academic writing problems and the benefits of artificial intelligence tools: A descriptive review - Zanyar Nathir Ghafar; Bareq Raad Raheem (Journal of Language and Pragmatics Studies, 2025)
Artificial Intelligence (AI) today represents not only technological advancement but also a powerful tool that is rapidly transforming the process of learning English. EFL learners increasingly use AI-based applications to enhance their language skills and academic writing performance. This study aims to identify the major challenges EFL learners face in academic writing and to highlight the significance of AI tools in addressing these issues. A qualitative descriptive review was conducted to achieve the study objectives. Relevant literature published over the last ten years was selected from open-access sources and academic databases. The findings indicate that learners encounter persistent problems in grammar, punctuation, coherence, and the organization of ideas. The review also shows that AI tools play a supportive role in helping learners improve their grammatical accuracy, expand their vocabulary, and develop better writing structure and coherence.